Microthrombi as a Major Cause of Cardiac Injury in COVID-19: A Pathologic Study - Pellegrini, Dario; Kawakami, Rika; Guagliumi, Giulio; Sakamoto, Atsushi; Kawai, Kenji; Gianatti, Andrea; Nasr, Ahmed; Kutys, Robert; Guo, Liang; Cornelissen, Anne; Faggi, Lara; Mori, Masayuki; et al. (Circulation (New York, N.Y.), 2021)
Cardiac injury is common in patients who are hospitalized with coronavirus disease 2019 (COVID-19) and portends poorer prognosis. However, the mechanism and the type of myocardial damage associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remain uncertain. We conducted a systematic pathological analysis of 40 hearts from hospitalized patients dying of COVID-19 in Bergamo, Italy, to determine the pathological mechanisms of cardiac injury. We divided the hearts according to presence or absence of acute myocyte necrosis and then determined the underlying mechanisms of cardiac injury. Of the 40 hearts examined, 14 (35%) had evidence of myocyte necrosis, predominantly of the left ventricle. Compared with subjects without necrosis, subjects with necrosis tended to be female, have chronic kidney disease, and have shorter symptom onset to admission. The incidence of severe coronary artery disease (ie, >75% cross-sectional narrowing) was not significantly different between those with and without necrosis. Three of 14 (21.4%) subjects with myocyte necrosis showed evidence of acute myocardial infarction, defined as ≥1 cm area of necrosis, whereas 11 of 14 (78.6%) showed evidence of focal (>20 necrotic myocytes with an area of ≥0.05 mm but <1 cm ) myocyte necrosis. Cardiac thrombi were present in 11 of 14 (78.6%) cases with necrosis, with 2 of 14 (14.2%) having epicardial coronary artery thrombi, whereas 9 of 14 (64.3%) had microthrombi in myocardial capillaries, arterioles, and small muscular arteries. We compared cardiac microthrombi from COVID-19-positive autopsy cases to intramyocardial thromboemboli from COVID-19 cases as well as to aspirated thrombi obtained during primary percutaneous coronary intervention from uninfected and COVID-19-infected patients presenting with ST-segment-elevation myocardial infarction. Microthrombi had significantly greater fibrin and terminal complement C5b-9 immunostaining compared with intramyocardial thromboemboli from COVID-19-negative subjects and with aspirated thrombi. There were no significant differences between the constituents of thrombi aspirated from COVID-19-positive and -negative patients with ST-segment-elevation myocardial infarction. The most common pathological cause of myocyte necrosis was microthrombi. Microthrombi were different in composition from intramyocardial thromboemboli from COVID-19-negative subjects and from coronary thrombi retrieved from COVID-19-positive and -negative patients with ST-segment-elevation myocardial infarction. Tailored antithrombotic strategies may be useful to counteract the cardiac effects of COVID-19 infection.